Spectrum of Neuropathophysiology in Spinal Muscular Atrophy Type I. Issue 1 (January 2015) - Harding, Brian N.; Kariya, Shingo; Monani, Umrao R.; Chung, Wendy K.; Benton, Maryjane; Yum, Sabrina W.; Tennekoon, Gihan; Finkel, Richard S.
<x xml:space="preserve">Abstract</x> Abstract Neuropathologic findings within the central and peripheral nervous systems in patients with spinal muscular atrophy type I (SMA-I) were examined in relation to genetic, clinical, and electrophysiologic features. Five infants representing the full clinical spectrum of SMA-I were examined clinically for compound motor action potential amplitude and SMN2 gene copy number; morphologic analyses of postmortem central nervous system, neuromuscular junction, and muscle tissue samples were performed and SMN protein was assessed in muscle samples. The 2 clinically most severely affected patients had a single copy of the SMN2 gene; in addition to anterior horn cells, dorsal root ganglia, and thalamus, neuronal degeneration in them was widespread in the cerebral cortex, basal ganglia, pigmented nuclei, brainstem, and cerebellum. Two typical SMA-I patients and a milder case each had 2 copies of the SMN2 gene and more restricted neuropathologic abnormalities. Maturation of acetylcholine receptor subunits was delayed and the neuromuscular junctions were abnormally formed in the SMA-I patients. Thus, the neuropathologic findings in human SMA-I are similar to many findings in animal models; factors other than SMN2 copy number modify disease severity. We present a pathophysiologic model for SMA-I as a protein deficiency disease affecting a neuronal network with variable clinical thresholds. Because new treatment strategies improve survival of infants with SMA-I, a better understanding of these factors will guide future treatments.